Management system of occupational safety at ukrainian enterprises: international and european dimension - Tverytnykova, Elena; Demidova, Yu. Ye.; Drozdova, Tatyana (Національний технічний університет "Харківський політехнічний інститут", 2021)
The international and European experience in creating and improving integrated systems in the field of occupational safety and health on the basis of research regulatory documents of the International Organization for Standardization, European standards, national standards of Ukraine, industry and methodical documents on management of occupational safety and health of oil and gas complex enterprises is overviewed. The implementation features of OHSAS 18001 and ISO 45001 international standards to create an integrated safety management system of professional activity have been studied. The ways of implementing the analyzed requirements in the industry safety standards of occupational activity of oil and gas complex enterprises of Ukraine are considered. A number of hazardous events related to occupational activity at the enterprises: industrial safety, technogenic safety, labour hygiene and safety, ecological safety, psychophysiological safety has been considered and a generalizing scheme of dangers and hazardous events has been created. A model of an integrated management system for occupational safety activities for oil and gas enterprises is proposed based on the involvement of scientific literature, regulatory documents using the structural-logical method, systematization and generalization, and methods of meaningful and comparative analysis. It is proved that the management system, based on the principles of the cyclical model of quality management by E. Deming should include such aspects as: quality and risk management, environmental mana gement, occupational safety management, social responsibility and power management.

Узагальнено міжнародний та європейський досвід зі створення та удосконалення інтегрованих систем в галузі безпеки праці та охорони здоров’я на основі дослідження нормативних документів Міжнародної організації стандартизації, європейських стандартів, національних стандартів України, галузевих та методичних документів з управління охороною праці та виробничої безпеки підприємств нафтогазового комплексу. Вивчено особливості впровадження міжнародних стандартів серії OHSAS 18001 та ISO 45001 щодо створення інтегрованої системи менеджменту безпеки професійної діяльності. Розглянуто шляхи впровадження проаналізованих вимог у галузеві стандарти безпеки професійної діяльності підприємств нафтогазового комплексу України. Розглянуто низку небезпечних подій, пов’язаних з професійною діяльністю на підприємствах: промислова безпека, техногенна безпека, гігієна та безпека праці, екологічна безпека, психофізіологічна безпека та створено узагальнюючу схему небезпек та небезпечних подій. Запропоновано модель інтегрованої системи менеджменту безпеки професійної діяльності для підприємств нафтогазового комплексу на основі залучення наукової літератури, нормативно-правових документів з застосуванням структурно-логічного методу, систематизації та узагальнення та методів змістовного та порівняльного аналізу. Доведено, що система менеджменту, засновуючись на принципах циклічної моделі управління якістю Е. Демінга повинна включати такі аспекти, як: управління якістю та ризиками, екологічне управління, менеджмент безпеки професійної діяльності, соціальна відповідальність, енергоменеджмент.
Система менеджменту безпеки професійної діяльності на підприємствах України: міжнародний та європейський вимір
Keywords: occupational safety; oil and gas complex; integrated management system; промислова безпека; нафтогазовий комплекс; інтегрована система управління